As dramaturgias comunitárias em uma atriz - Silva, Takaiúna Correia da (2021)
A communitarian actress is necessarily a dramaturge. The misery deriving from the privileges of a few are a immense daily disgrace for peripheral lives, as well as for the environment - deep marcs, unfortunately almost always irreparable. An actress in the community cannot run away from these various everyday deaths, instead she will have to learn how to tell stories, in order to, at least delay the death of sensibility. We are kind of griot and we tell stories in order to revel our lives, which are hidden by “normality “of poverty. It is a matter of surviving the confrontations of everyday life. In this dissertation I present an account of Community Theater from the trajectory of an actress and her dramaturgies - which means the territories within my body whenever it is ready for acting. From de innumerous dimensions that communitarian dramaturgy bring fourth, three of them has been listed: the territory of the actress, the territory of the art and the territory of the community - which are addressed in the third part of the dissertation. The territories here are not separated such as they are found in a map, there not necessarily a place where life begins and dramaturgy ends. The dramaturgy emerges more precisely in the borders of those territories. For that reason the frontier thoughts and the encounters are the devices of my writing, so that the stories (not only them) can be told in the communitarian dramaturgies. The text of the dissertation is articulated in three narrative movements: the first one is geared toward the communitarian being, a way of being an artist and how to relate with the territories. In the second movement I propose some outlines for the turbulences or crises in the path of a communitarian actress, searching for a draft of how these movements and states are constitutive in the actress’s dramaturgy. A communitarian actress is always rushing around in order to avoid death reaching her body. But as she rushes around she keeps on saying her text. When death eventually should reach her - and she knows it will - it must catches her open mouthed. (It will always continue)